State adaptation reserves cardiorespiratory system first-year students with varying degrees of physical fitness in terms of treadmill test - Levchenko, V.A.; Bublyk, S.A.; Drapchak, I.M.; Faichak, R.I.; Vashkevych, S.I. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : to examine the state of the cardiorespiratory system in terms of the stress test in first-year students with different levels of fitness. Material : the study involved 43 students, of which 18 boys and 25devushek basic medical group. The study used a treadmill, a pulse oximeter, spirometer. Results : more adjustment disorders were detected in students that are not involved in physical education at school. Decreased ability of the cardiorespiratory system to maintain proper oxygen supply of the organism in the stress test. This is not observed in students who were attending school in addition sports clubs. Found that students with low tolerance to physical exercise need a separate program of physical training, the dynamic control of the teachers and the need for additional medical examination. Conclusions : the treadmill test is an ideal way of revealing hidden maladjustment cardiorespiratory system in adolescence.